TEOLOGI KERUKUNAN DALAM KONTEKS PLURALITAS AGAMA - Muhammad Kursani Ahmad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2010)
The plurality of religion is undeniable and it should be theologically un-derstood as civilized relations among different religions and beliefs. Theo-logical dialogue is needed to establish mutual understanding and peacefulrelations among religions. This theology is called ‘theology of harmony’ inwhich one can put his/her faith in the same line with faith of other people.